Verification of EZH2 as a druggable target in metastatic uveal melanoma - Jin, Bei (Mol Cancer, 2020)
BACKGROUND: Hepatic metastasis develops in ~ 50% of uveal melanoma (UM) patients with no effective treatments. Although GNAQ/GNA11 mutations are believed to confer pathogenesis of UM, the underlying mechanism of liver metastasis remains poorly understood. Given that profound epigenetic evolution may occur in the long journey of circulating tumor cells (CTCs) to distant organs, we hypothesized that EZH2 endowed tumor cells with enhanced malignant features (e.g., stemness and motility) during hepatic metastasis in UM. We aimed to test this hypothesis and explore whether EZH2 was a therapeutic target for hepatic metastatic UM patients. METHODS: Expression of EZH2 in UM was detected by qRT-PCR, Western blotting and immunohistochemistry staining. Proliferation, apoptosis, cancer stem-like cells (CSCs) properties, migration and invasion were evaluated under circumstances of treatment with either EZH2 shRNA or EZH2 inhibitor GSK126. Antitumor activity and frequency of CSCs were determined by xenografted and PDX models with NOD/SCID mice. Hepatic metastasis was evaluated with NOG mice. RESULTS: We found that EZH2 overexpressed in UM promoted the growth of UM; EZH2 increased the percentage and self-renewal of CSCs by miR-29c-DVL2-β-catenin signaling; EZH2 facilitates migration and invasion of UM cells via RhoGDIγ-Rac1 axis. Targeting EZH2 either by genetics or small molecule inhibitor GSK126 decreased CSCs and motility and abrogated the liver metastasis of UM. CONCLUSIONS: These findings validate EZH2 as a druggable target in metastatic UM patients, and may shed light on the understanding and interfering the complicated metastatic process.